2023
DOI: 10.1186/s12872-023-03094-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between red blood cell distribution width-to-albumin ratio and prognosis of patients with acute myocardial infarction

Abstract: Background Red blood cell distribution width (RDW) and albumin level were considered to be related to the prognosis of patients with acute myocardial infarction (AMI). This study aims to investigate the correlation between RAR and 90-day mortality in AMI patients. Methods Data of AMI patients were obtained from the Medical Information Mart for Intensive Care III (MIMIC-III) database. According to the median, RAR < 4.32 was regarded as low RAR le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…The rate of erythrocyte destruction and the release of immature erythrocytes into the circulation are also increased by oxidative stress, consequently leading to an increase in RDW values. Serum albumin, a vital protein with anti-inflammatory, nutritional, and hematological characteristics, effectively suppresses platelet activation and aggregation [25]. Serum albumin is traditionally evaluated to assess the nutritional status of patients who are critically ill. Hypoproteinemia is regarded as a dependable indicator of prognosis in numerous critically ill patients with chronic conditions [26].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of erythrocyte destruction and the release of immature erythrocytes into the circulation are also increased by oxidative stress, consequently leading to an increase in RDW values. Serum albumin, a vital protein with anti-inflammatory, nutritional, and hematological characteristics, effectively suppresses platelet activation and aggregation [25]. Serum albumin is traditionally evaluated to assess the nutritional status of patients who are critically ill. Hypoproteinemia is regarded as a dependable indicator of prognosis in numerous critically ill patients with chronic conditions [26].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated RDW has been associated not only with vascular risks, but also with the prognosis and risks of complications of various cancers, such as breast, lung, and esophageal cancers [44][45][46][47][48]. Recently, RDW has been reported as a potentially useful biomarker to predict prognosis and complication risks in hematologic cancers, such as diffuse large B-cell lymphoma, primary central nervous system lymphoma, multiple myeloma and chronic myeloid leukemia [49][50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in cardiovascular disease, vascular endothelial disorder causes elevated RDW [20][21][22][23]. Moreover, it has been reported that elevated RDW level is associated not only with vascular risks, but also prognosis of various cancers, such as breast cancer, lung cancer, and esophageal cancer [39][40][41][42][43][44]. However, the connection between RDW in hematological malignancy and cellular therapy has been unclear [45].…”
Section: Discussionmentioning
confidence: 99%